Local Characteristics Shape the Intended Political Behaviours of Adolescents - Daniel Deimel; Hermann J. Abs (Social Indicators Research, 2021)
Among the different factors that predict political participation, the characteristics of the local community are often described. The types and the intensity of political participation differ in urban and rural communities. The local community provides social and cultural resources for political participation and at the same time acts as a driver of political socialisation. The political attitudes of adolescents differ depending on the characteristics of the communities in which they live, i.e. the local context of their political socialisation. This paper describes the context of the political socialisation of adolescents in the German federal state of North Rhine-Westphalia (NRW) in terms of geographical differences in socioeconomic, sociostructural, and sociocultural characteristics. The approach uses public databases to construct indicators that describe administrative districts in terms of their degree of urbanisation, degree of aggregated individual wealth, and variety of opportunity. These indicators were merged with the NRW subset of the International Civic and Citizenship Education Study (ICCS 2016), which comprises N0.167em=0.167em1451 students in N0.167em=0.167em59 schools. Neither the degree of urbanisation nor the degree of aggregated individual wealth was suitable for explaining differences in the intended political behaviour of secondary school students in the 8th grade in NRW. However, the higher the variety of opportunity in a certain district, the less frequently students intend to participate in elections as adults. Also, the higher the measure, the more frequently students intend to participate in illegal protest activities. Apparently certain local environments mobilise intentions to participate in protest activities and suppress more conventional political activities.
Keywords: 300; Regional characteristics; Political socialisation; Intended political behaviour; Conventional political participation; Political protest